2010
DOI: 10.1145/1902593.1902599
|View full text |Cite
|
Sign up to set email alerts
|

Move, Beam, and Check! Imagineering Tangible Optical Chess on An Interactive Tabletop Display

Abstract: This article presents Tangible Optical Chess, a tangible version of Optical Chess, a strategy game implemented on an interactive tabletop display. We discuss the design and implementation of both systems and report our evaluation game play sessions and our observations during the open house demonstration events at our research center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Games that are based on tangible user interfaces and interactive tabletops have often been the focus for investigations, for example STARS [13], Weathergods [1], PINS [8], Inc-reTable [10], Optical Chess [20], Comino [11] or Futura [16]. However, only few have been done for active tangible interaction.…”
Section: Related Workmentioning
confidence: 99%
“…Games that are based on tangible user interfaces and interactive tabletops have often been the focus for investigations, for example STARS [13], Weathergods [1], PINS [8], Inc-reTable [10], Optical Chess [20], Comino [11] or Futura [16]. However, only few have been done for active tangible interaction.…”
Section: Related Workmentioning
confidence: 99%
“…A body of literature explores the opportunities offered by MTIs and TUIs to edutainment and entertainment in various fields, from classroom collaborative learning [12] [40][2] to children's decision making and cooperation support [8], interactive storytelling [13] [14], pervasive games [15] and museum exhibits [16] [17]. While most of these approaches rely on large interactive displays, commercial MTI-TUI games developed for mobile devices are becoming increasingly available [49] [51].…”
Section: Introductionmentioning
confidence: 99%
“…Examples can be found in [10], which describes a game developed for children with cerebral palsy, or in [11], where VR training based on a tabletop game was proved to be a viable adjunct to conventional physical therapy in facilitating motor learning in patients with traumatic brain injuries. Other research showed the capabilities of entertainment and edutainment applications based on tabletop interactive interfaces in various fields, from classroom collaborative learning [12] to interactive storytelling [13] [14], pervasive games [15] and museum exhibits [16] [17].…”
Section: Introductionmentioning
confidence: 99%